(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
Antimicrobial susceptibility and coagulase typing of Staphylococcus aureus isolates, with particular emphasis to Methicillin Resistant S. aureus (MRSA), were studied among strains isolated from various types of specimens collected at Mymensingh. A newly developed panel of anti-sera against different coagulase enzymes was used for coagulase typing. The study included 79 strains of S. aureus and of those, 40 were identified as MRSA on the basis of resistance to oxacillin (1 gm) discs. The rate of resistance of S. aureus to different antibiotics observed: penicillin (88.61%), oxacillin (48.10%), cephradine (44.30%), gentamicin (27.85%), erythromycin (34.18%), fusidic acid (25.0%) and rifampicin (20.0%). None of the isolates showed vancomycin resistance. Both MRSA and non-MRSA strains were found belonging to Coagulase type VI. Drug resistance pattern and coagulase type of MRSA strains indicated a homogenous epidemiologic origin that needs further exploration including strains from different geographic locations. Bangladesh J Med Microbiol 2007; 01 (02): 56-60